Accounting for the Green Economy: Integration of Biological Asset Accounting and Green Accounting Practices in Horticultural SMEs in Sikka Regency - Mitan, Wilhelmina; Noeng, Amanda Yecci (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study aims to evaluate gaps in biological asset and environmental accounting practices in horticultural SMEs in Sikka Regency and to develop an integration model suitable for these SMEs' characteristics. This study uses a mixed-methods approach, combining qualitative analysis through in-depth interviews and documentation with quantitative analysis to measure the gaps between existing practices and applicable accounting standards. The research results indicate that most SMEs have not adopted PSAK 69 standards on the recognition and measurement of biological assets, and that they lack environmental cost recording in their financial statements. Based on these findings, this study develops an integrated model of biological asset accounting and environmental accounting, which is expected to enhance transparency and accountability and support the principles of a green economy in SME practices. This model is expected to help SMEs produce more accurate, relevant, and sustainable financial statements, thereby supporting environmentally friendly strategic decision-making.